Evaluation of the growth rates and related prognostic factors in radiation-induced meningiomas - Entenmann, Christian Joachim; Bubeníková, Adéla; Blažková, Jana; Zápotocký, Michal; Kruseová, Jarmila; Sumerauer, David; Trková, Kateřina; Sochová, Vladimíra; Koblížek, Miroslav; Kynčl, Martin; Malinová, Běla; Bradáč, Ondřej; et al. (Journal of neuro-oncology, 2023)
PURPOSE: Literature dedicated to growth patterns and growth rate influencing factors of radiation-induced meningiomas (RIMs) is limited. To deliver new insights into the topic, a volumetric growth analysis of RIMs was performed. METHODS: This single-center, retrospective cohort study included patients diagnosed with intracranial meningioma who received radiation treatment at least > 5 years before the RIM diagnosis. Volumetric analysis of individual RIMs was performed using 3D volumetry at the time of RIM diagnosis and during follow-up. RIM growth was determined by calculating absolute (AGR), and relative (RGR) growth rates. Prognostic factors associated with RIM growth were evaluated. RESULTS: A total of 26 patients with 33 meningiomas were enrolled in the study and radiologically/clinically followed up during a median duration of 5.6 years (IQR 3.9-8.8 years). Median AGR was 0.19 cm3 per year and the median RGR was 34.5% per year. Surgically managed RIMs were more likely fast-growing compared to observed ones based on the AGR (p < 0.002). The recurrence rate after total resection was 14.3%. Younger age at RIM diagnosis was associated with higher tumor growth (RGR ≥ 30%, p = 0.040). A significant correlation was found between the length of latency period and the RGR (p = 0.005). CONCLUSION: To diagnose RIM as early as possible comprehensive MRI surveillance is required. Younger patients with shorter latency periods may profit from shortened MRI intervals, with further management being dependent on the growth rate and eventual symptomatology.
Keywords: Neoplasms, Radiation-Induced; prognóza; meningeom; Meningeal Neoplasms; Prognosis; Volumetry; lidé; retrospektivní studie; Growth; Meningioma; Radiation therapy; Retrospective Studies; Radiation-induced meningioma; meningeální nádory; Childhood tumor; nádory vyvolané zářením; Humans